The effect of Al substitution on the structural and magnetic properties of epitaxial thin films of epsilon ferrite. (November 2017) - Corbellini, Luca; Lacroix, Christian; Ménard, David; Pignolet, Alain
Abstract: Epitaxial growth of aluminum substituted epsilon ferrite by pulsed laser deposition on strontium titanate and yttrium-stabilized zirconium substrates is demonstrated for a wide range of aluminum substitution. Linear decrease of the out-of-plane lattice parameter with aluminum substitution correlates with the decrease of the coercive magnetic field, while the magnetization first increases and then decreases with increasing aluminum concentration. A characteristic inflexion in the hysteresis loops has been attributed to the presence of a small quantity of magnetite. Epitaxial growth on yttrium-stabilized zirconium is technologically significant due to its use as buffer layer for the growth of complex oxides on silicon. Graphical abstract: